Using codesign focus groups to develop an online COmmunity suPporting familiEs after Sudden Cardiac Death (COPE-SCD) in the young. Issue 8 (5th August 2022) - Yeates, Laura; Gardner, Karen; Do, Judy; van den Heuvel, Lieke; Fleming, Gabrielle; Semsarian, Christopher; McEwen, Alison; Adlard, Leesa; Ingles, Jodie
Abstract : Objective: To codesign an online support intervention for families after sudden cardiac death (SCD) in the young (<35 years). Design: Codesign of an SCD family intervention by stakeholder focus groups. Setting: Families and healthcare professionals with experience in SCD in the young. Participants: Semistructured online focus groups were held with key stakeholders, that is, family members who had experienced young SCD, healthcare professionals and researchers based in New South Wales, Australia. Guided discussions were used to develop an online support intervention. Thematic analysis of discussions and iterative feedback on draft materials guided content development. Results: Four focus groups were held (4–6 participants per group, 12 unique participants). Stakeholder involvement facilitated development of high-level ideas and priority issues. Creative content and materials were developed based on user preference for stories, narratives and information reflecting everyday experience of families navigating the legal and medical processes surrounding SCD, normalising and supporting grief responses in the context of family relationships and fostering hope. Emphasis on accessibility led to the overarching need for digital information and online engagement. These insights allowed development of an online intervention—COPE-SCD: A COmmunity suPporting familiEs after Sudden Cardiac Death—which includes a website and online support programme. Conclusion: Using codesign with stakeholders we have developed a support intervention that addresses the needs of SCD families and aims to fill a large gap in existing healthcare. We will evaluate COPE-SCD to determine whether this is an effective intervention for support of families following a young SCD.